Sistem Informasi Desain Grafis Produk DKV Daily - Muhammad Irfan; Jullend Gatc (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
DKV Daily is a community or organization engaged in visual design located in Cipete area, South Jakarta, which does not have a product contest yet. The design process and design can only be done verbally or by telephone. In practice, this process takes a long and long time. Besides this manufacturing process is not accompanied by a complete catalog, but only through social media. This study aims to build website applications that provide benefits to the DKV Daily in facilitating the search for designers who want to open up opportunities in a design according to the needs of consumers. System development is carried out with the System Development Life Cycle using prototyping methods. In addition this study uses Unified modeling language as a modeling of the system. Program development in this application uses PHP, HTML, and CSS. The results of this study are in the form of a website for Clients, Designers, and Admins. Based on the results of testing and evaluation, the product application is declared in accordance with user requirements and can be used as a graphic design product application.